Particle Swarm Optimization-Based Recloser Placement for Reliability Improvement in the Kuala ULP Distribution System - Ramdhan Halid Siregar; Ardiansyah Putra Karo; Syahrizal (Indonesian Journal of Technical and Vocational Education Training, 2025)
In an electric power distribution system, one of the things that needs to be considered is the reliability of the electric power system. Currently, the location of the recloser is very important for the reliability of the power system. The parameters used for network reliability are the SAIFI and SAIDI values. The SAIFI and SAIDI values can be determined based on the failure time and failure rate in one year. The smaller the SAIFI and SAIDI values, the better the reliability. The purpose of this study is to determine the best recloser position on the MG 03 ULP Kuala feeder grid, Langkat Regency. The method chosen in determining the research location uses particle swarm optimization (PSO) by implementing MATLAB R2021a software. The simulation results show that the reliability before and after reinstallation has changed. SAIFI and SAIDI before reintegration are 1.2495 hours/customer/year and 3.3555 times/customer/year, respectively.